Prediction of Fatigue Crack Growth Rate and Stress Intensity Factors Using the Finite Element Method - Yahya Ali Fageehi (Advances in Materials Science and Engineering)
This study investigates crack growth and stress intensity factors via finite element methods in linear elastic fracture mechanics. The procedure involves estimating stress intensity factors (SIFs), crack trajectory, and fatigue life, using two different softwares in both two and three-dimensional analyses. Crack modeling was done in a variety of ways depending on the software. ANSYS Mechanical R19.2 and FRANC2D/L software were used to prognosticate fatigue crack growth, fatigue life, and associated stress intensity factors under plane stress state. Fatigue analysis was governed by Paris’s law and crack growth direction by the theory of maximum circumferential stress. The results show that the fatigue growth was attracted to the hole and either changes its direction to reach the hole or floats by the hole and grows as the hole is missed. The findings of the study agree with other experimental and numerical crack propagation studies presented in the literature.